2007
DOI: 10.1007/s11250-007-9051-z
|View full text |Cite
|
Sign up to set email alerts
|

Treatment with an intravaginal progestagen and estradiol to prevent prolonged anestrus in crossbred zebu cows under tropical conditions

Abstract: To study the effectiveness of a treatment with an intravaginal progestagen in combination with estradiol-17beta (E-17beta) on estrus induction, prevention of prolonged anestrus and fertility in noncycling crossbred zebu cows, a trial was conducted in a farm in Zulia state, Venezuela. Fifty noncycling suckled crossbred cows (B. taurus x B. indicus) with 60 dpp were randomly allotted to one of the following treatments: MAP+E-17beta (n=22), intravaginal device (250 mg of MAP) during 7 days + 50 mg of MAP and 5 mg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 22 publications
0
2
0
Order By: Relevance
“…Higher pregnancy rates were found by using the same AI protocol, but without differences with the control treatment inseminated after VO of natural estrus [ 23 25 ]. On the other hand, [ 26 ] working with zebu synchronized animals and FTAI at 48 and 72 hours, they classified estrus intensity according to the number of mounts as high (≥20) and low (<20) without estrus by continuous VO; they detected 68.4% of cows in estrus; the overall pregnancy rate was only 25.4%; communicating these authors that 63.8% of the cows that did not show estrus, in fact ovulated, the functional biological phenomenon known as both silent estrus and ovulation occurred; on the other hand, 85.9% of cows with detected estrus ovulated, resulting in a 14% of cows showing the phenomenon known as an-ovulatory estrus which also has been reported for crossbred cows [ 27 ]; it is then possible to assume that the use of the QAM as the only single sign of sexual behavior is not efficient enough to detect cows in estrus in the warm tropics and supports what has recently been reported using rating tables considering other secondary signs as well [ 16 ], in accordance with the highest efficiency using a scale with seven signs, reported by [ 28 ]; and the possibility of more effectively predicting ovulation time by using a scale of points with the estrus signs [ 11 , 14 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Higher pregnancy rates were found by using the same AI protocol, but without differences with the control treatment inseminated after VO of natural estrus [ 23 25 ]. On the other hand, [ 26 ] working with zebu synchronized animals and FTAI at 48 and 72 hours, they classified estrus intensity according to the number of mounts as high (≥20) and low (<20) without estrus by continuous VO; they detected 68.4% of cows in estrus; the overall pregnancy rate was only 25.4%; communicating these authors that 63.8% of the cows that did not show estrus, in fact ovulated, the functional biological phenomenon known as both silent estrus and ovulation occurred; on the other hand, 85.9% of cows with detected estrus ovulated, resulting in a 14% of cows showing the phenomenon known as an-ovulatory estrus which also has been reported for crossbred cows [ 27 ]; it is then possible to assume that the use of the QAM as the only single sign of sexual behavior is not efficient enough to detect cows in estrus in the warm tropics and supports what has recently been reported using rating tables considering other secondary signs as well [ 16 ], in accordance with the highest efficiency using a scale with seven signs, reported by [ 28 ]; and the possibility of more effectively predicting ovulation time by using a scale of points with the estrus signs [ 11 , 14 ].…”
Section: Resultsmentioning
confidence: 99%
“…Some authors [ 23 25 ] have reported a low estrus detection rate for control cows subjected to AI (extreme values: 22.9% to 31.8%), which may be attributable to the traditional estrus detection system based VO of the QAM as the only sign of estrus; the small number and wide separation between two observations in a twelve-hour period; and the lack of trained personnel to recognize, to record, and to rank other secondary and important signs of this natural or induced physiological state, including the detection, recording, and tracking of sexual social events of formation of the active sexual groups, published by [ 3 ] for the DP cattle, which was reported as novel sign of estrus in specialized dairy herds [ 29 ]. System practices for the identification of the cow in estrus for crossbred populations that would indicate an inefficient estrus detection, which is identified as the most important factor limiting fertility of cattle in the world [ 9 ].…”
Section: Resultsmentioning
confidence: 99%